Sistem Informasi Penjualan Badan Usaha Milik Desa Tulap Berbasis Web Menggunakan Framework Laravel - Refandi Andika Runtu; Gladly Caren Rorimpandey; Quido Conferti Kainde; Mohamad Ramdhan Arif Kaluku (JOINTER : Journal of Informatics Engineering, 2021)
Tulap Village is one of the villages in Minahasa that has a Village-Owned Enterprise (BUMDES). In marketing activities, the products sold are still only offered to families, local communities, and tourist attractions in Tulap Village. Marketing outside the village must be carried out in cities such as Manado and Bumdes is looking for a place to sell these products. The rental service for goods is still limited to the surrounding community because information about the business is not yet available. The system development carried out in this study uses the Waterfall model (Pressman, 2010). System modeling is documented using Data Flow Diagrams (DFD). The result of this research is a sales information system that can help customers see the products being sold or the goods rented by BUMDes Tulap. Testing this system using the blackbox and whitebox testing method.